ANALYSIS OF FISHING TECHNOLOGY AND FISH PRODUCTION BY WOMEN IN SMALL-SCALE FISHING ENTERPRISE IN OGUN WATERSIDE LGA, OGUN STATE, NIGERIA - IDOWU, A.A; JENYO-ONI , A; OLAOYE, O.J; OJELADE, O.C; EL-IMAM, K.A. (Nigerian Journal of Fisheries, 2015)
This study was conducted to evaluate the productivity, profitability and level of technology of artisanal women in small scale fishing enterprises in Ogun Waterside Area, Ogun State, Nigeria. A well-structured interview guide was used to collect primary data from one hundred and twenty respondents from five fishing communities (Iwopin, Idaleketa, Makun-omi, Agbalegiyo and Ode-Omi) based on their fishing activities. The information collected was analyzed using descriptive statistics. The result revealed that (74.2%) were in the active age distribution of 30- 50 years, 33.3% have no formal education while 45.0% were in the bracket of 21-30 years fishing experience, 83.3% of the respondents were married and 91.7% were not members of any fishery society. The result also showed a gross margin of N29,989.44 and a net income of N2,431.93 which could be attributed to their performance. There was a significant relationship between constraints faced by the fisher women and the size of the business. Implications of these findings were critically examined, and pertinent recommendations were proffered based on the salient findings in the study.